Pengaruh Komitmen Profesional, Pengalaman Kerja, Dan Kode Etik Terhadap Pengambilan Keputusan Etis Konsultan Pajak di Pekanbaru - Rozi Aulia Rahman; Rudi Syaf putra; Dwi Fionasari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study focuses on how tax consultants in Pekanbaru make ethical decisions in relation to their job experience, professional dedication, and code of ethics. With primary data gathered via surveys, this study employs quantitative methodologies. Forty-two people answered the questionnaire, and the study's sample was saturated. This study used the t test, the coefficient of determination (R2) analysis test, the validity and reliability test, the classical assumption test, and hypothesis testing as its data analysis methods. The study's findings show that professional dedication and adherence to a code of ethics influence tax consultants' ethical decision-making, but job experience has bearing on it.